Ovulation rates and twinning birth following Follicle Stimulating Hormone (FSH) treatment at differents stages of estrus cycle - Polmer Situmorang; D.A Kusumaningrum; R Sianturi (Indonesian Center for Animal Research and Development (ICARD), 2012)
Twinning rate could be increased through genetically approach or through hormonal induction approach. The aim of this study was to observe the effect of first injection of FSH initiated on the ovulation rate. The experiment design was completely randomized with 3 different time of FSH was initiated as treatment using 12 lactating dairy cattle. Injection of FSH was initiated at day 2 (Treatment I), day 10 (Treatment II) and at day 18 (Treatment III) of estrus cycle. A total of 6 ml Folltropin (Equivalent 120 mg FSH) was intramussculary injected in decreasing dossis method twice a day with 12 hours interval for 4 days. Blood was collected on day 12 of estrus cycle for progesterone level. Data recorded were the diameter of ovary (DO), total corpus luteum (TCL), concentration of progesterone (P), percentage of pregnancy and number of birth. The means DO, TCL and P were significantly (P < 0.05) higher after injection (2.0 cm; 2.1 and 1.6 ng/ml) than those before injection (1.4 cm, 1.0 dan 0.6 ng/ml). The time of first injection of FSH was initiated, significantly affect the ovulation rate. The mean DO, TCL and P were significantly higher (P < 0.01) in treatment II (2.6 cm; 4.0 and 2.9 ng/ml) than those in treatments I (1.9 cm; 1.3 and 0.9 ng/ml) or in treatment III (1.6 cm; 1.3 and 0.9 ng/ml). There was no significant diference between treatment I and III. The percentage of pregnant were 25.0; 75.0 and 25.0 for treatments I; II and III respectively. One twin birth and 1 single birth were obtained in treatments II but only one single birth for each treatment I and III. Number of CL were positively correlated with the concentration of progesterone but were not fully useful for prediction number of birth. In conclusion, the dairy cattle gave a better response to exogenous gonadotropin hormone when the first injection was initiated at day 10 of estrus cycle. Key Words: Hormone, FSH, Estrus Cycle, Ovulation, Twin Birth